SURVEI PELAKSANAAN PEMBELAJARAN PERMAINAN TRADISIONAL DI SEKOLAH DASAR NEGERI 6 SUNGAI PINYUH - Ramadhani, Rheza Alamsyah; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Traditional games at this time are rarely done even traditional games are almost forgotten and rarely participate in competitions. The absence of teacher innovation and creativity will result in children feeling bored, less enthusiastic, and unable to foster joy and fun in children. The purpose of this study was to find out how the implementation of traditional game learning at SDN 6 Sungai Pinyuh and the desire / interest of students in traditional games at SD Negeri 6 Sungai Pinyuh. The research method used in this research is descriptive quantitative method. Descriptive research aims to provide an overview of learning traditional games at SDN 6 Sungai Pinyuh. Data analysis with a quantitative approach was used to analyze the data from the questionnaire. The results of the traditional game research can be said to be "good" with an overall score of 1) 1st grade elementary school students 73% can be said to be "good 2) 2nd and 3rd grade elementary school students 95% can be said to be "very good" 3) 4th grade elementary school students 91% can said to be "very good" 4) grade 5 and 6 elementary school students 94% can be said to be "very good"